Implementasi Kontrol Lampu dan Kipas Secara Implisit Menggunakan Suara Dengan Metode Text Processing Berbasis Embedded System - Wildo Satrio; Dahnial Syauqy; Hurriyatul Fitriyah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Voice technology can be used as a control over various types of electronic equipment, including lights and fans. In its application the sentence used for control of the equipment is limited and must know what sentence can be used to use the system. Based on this problem, control fan and lights with implicitly command using voice. Arduino as a control system for lights and fans by using Android for sound processing with text processing methods. Voice data entered via Android is converted to text. Each sentence-shaped text is separated into unit words. Then each word is matched with a database that has been created previously using the stopword removal wordlist algorithm. The matching results are sent to Arduino and the data is processed to produce output in the form of light and fan control. From the test results, this system has a 100% success value in functional testing and testing of user voice input processing. In testing the success of the system to process the user's implicit sentence into the desired output, it has an accuracy of 96.67%. Furthermore, to test the performance of the application to process sentences, the system has an average time of 1 second increase according to the many words entered, while the sentence processing process increases by 200 nano seconds along with the number of input words.